Geokimia (XRF) Batuan Andesit Desa Biluhu Barat, Kecamatan Biluhu, Kabupaten Gorontalo - Hamid, Rinto Saputra; Arifin, Yayu Indriati; Akase, Noviar (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the geochemical characteristics of andesite rocks within the Tinombo Formation located in Biluhu Barat Village, Biluhu District, Gorontalo Regency. Data collection was conducted through geological mapping and geochemical analysis using X-Ray Fluorescence (XRF) to determine the magma series, magma type, and tectonic setting of the rock origin. The results show that the study area consists of porphyritic andesite and granodiorite units. Geochemical data indicate that the andesite rocks belong to the calc-alkaline magma series, with rock types identified as andesite and basaltic andesite. Geochemical diagrams reveal that the rocks originated from an Island Arc Calc-Alkaline Basalt tectonic setting. The calculated magma source depth ranges from 156 to 164 km, indicating magmatic processes occurring within a subduction zone. This study contributes to a better understanding of the tectonic framework and magmatic evolution in the Gorontalo region.